Η ΜΗΔΕΙΑ ΤΗΣ ΜΑΡΘΑ ΓΚΡΑΧΑΜ: ΣΕΞΟΥΑΛΙΚΗ ΖΗΛΙΑ ΚΑΙ ΤΑ ΟΡΙΑ ΤΗΣ ΑΝΘΡΩΠΙΝΗΣ ΦΥΣΗΣ [MARTHA GRAHAM’S MEDEA: SEXUAL JEALOUSY AND THE LIMITS OF HUMAN NATURE] - Papathanasopoulou, Nina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This paper explores the radical rendering of Medea by the revolutionary choreographer Martha Graham in her 1946 work Cave of the Heart. Graham creates a unique portrayal of Medea by focusing on Medea’s emotional experience and gives memorable expression to the timeless feeling of jealousy to which Medea is subjected. Drawing on her pioneering dance technique, Graham examines emotion through unfamiliar movements of the body, showcases the overwhelming power of jealousy, and celebrates its intensity and importance. Graham’s Medea is powerful yet pitiful, inviting the audience to acknowledge, understand, and accept a woman’s emotional experience. I first discuss the early years of Graham’s career and the factors that led to her fascination with Greek myth. I then draw out similarities between Graham’s dances and Greek tragedy and analyze Graham’s innovative decisions to situate Medea in a gynocentric world, not to include the children, and to make Medea’s sexual jealousy the central theme. I conclude by suggesting that Graham creates a triumphant Medea, who asserts her power through her various subhuman and superhuman features. Using animal and nature imagery, Graham focuses on Medea’s emotional experience and brings out both her destructive nature and her ability to elicit our sympathy.